Using Intervention Mapping to Develop Health Education Components to Increase Colorectal Cancer Screening in Puerto Rico - Serra, Yolanda A.; Colón-López, Vivian; Savas, Lara S.; Vernon, Sally W.; Fernández-Espada, Natalie; Vélez, Camille; Ayala, Alelí; Fernández, María E. (Frontiers in Public Health, 2017)
Introduction Colorectal cancer (CRC) is a leading cause of cancer-related mortality in Puerto Rico (PR). Although largely preventable through screening and treatment of precancerous polyps, CRC screening rates in PR remain low while CRC incidence and mortality continue to increase. Methods We used intervention mapping (IM), a systematic framework using theory and evidence to plan a health promotion intervention to increase colorectal cancer screening (CRCS) among Puerto Rican adults 50 years and older who are patients of Federally Qualified Health Centers (FQHCs) in PR. Results To inform the development of a logic model of the problem during the needs assessment phase, we determined the CRC incidence and mortality rates in PR using recent data from the PR Cancer Registry, conducted a literature review to better understand behavioral and environmental factors influencing CRC among Hispanics in general and in Puerto Ricans, and collected new data. We conducted seven focus groups to identify community needs and resources, specific sub-behaviors related to CRCS (performance objectives) and the determinants of CRCS. We then developed matrices of change objectives that would guide the content, behavioral change method selection, and the practical applications that would be included in the program. We selected two overarching methods: entertainment education and behavioral journalism and developed practical applications, materials, and messages containing several other methods including modeling, persuasion, information, and tailoring. We developed and pretested a Tailored Interactive Multimedia Intervention, newsletter, an action plan, and supplemental print materials for patients. We also developed a patient mediated provider prompt to increase provider recommendation and improve patient provider communication. Conclusion The use of IM for systematic planning produced a detailed coherent plan for the CRCS educational intervention. Guided by IM processes, steps, and tasks, we used community level information, existing literature, theory, and new data to develop health education materials that were well received by the priority population and will likely increase CRCS among FQHC patients in PR.